Anti-bulge degradable leather plastic adhesive and preparation method thereof

By synergistically combining epoxy-terminated polyurethane emulsion with fluorine-free polar modified epoxy compound dispersion, along with silane complexes and cellulose nanocrystals, a dense and stable three-dimensional cross-linked network structure is constructed, solving the problems of insufficient anti-bubbling, bonding strength, and water resistance in leather and plastic adhesives, thus realizing the application of high-performance and environmentally friendly adhesives.

CN120924216APending Publication Date: 2025-11-11SHANGHAI JIUYUAN PETROCHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511462311.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing leather and plastic adhesives are inadequate in terms of anti-bubbling, bonding strength, and water resistance, making it difficult to meet the needs of high-performance applications.

Method used

By synergistically combining epoxy-terminated polyurethane emulsion with fluorine-free polar modified epoxy compound dispersion, along with silane complex and cellulose nanocrystals, a dense and stable three-dimensional cross-linked network structure is constructed. Through multiple interaction mechanisms such as chemical cross-linking, hydrogen bonding, and physical entanglement, the interfacial bonding strength and water resistance are enhanced.

Benefits of technology

It achieves an interfacial bonding strength of ≥12 MPa, a water vapor transmission rate of ≤4.0wt%, and a water absorption rate of ≤4.0wt%, significantly improving the adhesive's anti-bubbling performance and water resistance stability, while also exhibiting good biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924216A_ABST
    Figure CN120924216A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and provides an anti-bulge degradable leather plastic adhesive and a preparation method thereof.The anti-bulge degradable leather plastic adhesive is designed by adopting an epoxy-terminated polyurethane emulsion as a main body and adopting a composite formula of a fluorine-free polar modified epoxy compound dispersion liquid, starch acetate, a silane compound and cellulose nanocrystals as auxiliary materials. Through the processes of prepolymerization, end group sealing, modification reaction, cross-linking curing and the like, the synergistic effect among the components is realized, and the excellent performances that the interface bonding strength is greater than or equal to 12MPa, the water vapor transmission rate is less than or equal to 280g per square meter per day and the water absorption rate is less than or equal to 4.0% are realized; the technical problems that a traditional adhesive is poor in anti-swelling performance, insufficient in bonding strength and poor in water resistance are solved, and wide industrial application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials, specifically to a biodegradable leather-plastic adhesive for preventing blistering and its preparation method. Background Technology

[0002] With the rapid development of industries such as automotive interiors, furniture manufacturing, and apparel and bags, the application of leather-plastic composite materials in modern industry is becoming increasingly widespread. Especially in high-end car seats, fashion bags, and sports shoe materials, leather-plastic composite structures have become an important technical means to enhance product quality and functionality. In these applications, adhesives, as the key material connecting leather and plastic substrates, directly determine the overall quality and service life of the composite product. Given that leather-plastic composite products often face complex operating environments, including temperature and humidity changes, mechanical stress, and long-term exposure, stringent performance requirements are placed on adhesives. These requirements mainly include excellent anti-bubbling properties to resist interfacial failure in humid and hot environments, sufficient adhesive strength to withstand various mechanical loads, good water resistance to ensure stability in humid environments, and biodegradable properties that meet environmental requirements to adapt to the trend of green manufacturing. The development of adhesive technologies that meet these comprehensive performance requirements can not only significantly improve the quality and reliability of leather-plastic composite products and extend their service life, but also promote the transformation and upgrading of related industries towards high-end and environmentally friendly directions, possessing significant technological value and market significance.

[0003] However, the technological development of leather and plastic adhesives still faces many challenges and shortcomings. While traditional polyurethane adhesives possess certain bonding properties, they exhibit significant deficiencies in preventing blistering. This is primarily due to the lack of effective moisture-blocking groups in their molecular structure, leading to easy moisture penetration and accumulation in high-humidity environments, resulting in interfacial peeling and blistering. Simultaneously, the bonding strength of existing adhesives often falls short of the demands of high-performance applications. This is mainly due to an unreasonable cross-linking network structure design and a lack of effective intermolecular force enhancement mechanisms, resulting in insufficient interfacial bonding. Furthermore, poor water resistance is another common problem, fundamentally caused by an excessive number of hydrophilic groups or insufficient hydrophobic modification in the adhesive molecular chain, leading to swelling or degradation in aqueous environments. For example, Chinese Patent CN102002337B discloses a high-strength waterborne polyurethane adhesive, but it suffers from poor blistering prevention performance. Similarly, Chinese Patent CN105331328A discloses an environmentally friendly adhesive for plywood and its preparation method, but its bonding strength needs improvement. For example, Chinese patent CN112029448B discloses a water-based acrylic adhesive composition, but it has the drawback of unsatisfactory water resistance. Summary of the Invention

[0004] (1) Technical problems to be solved The purpose of this invention is to provide a biodegradable leather and plastic adhesive for preventing blistering and its preparation method, thereby solving the problems of insufficient anti-blistering properties, insufficient bonding strength, and poor water resistance of current adhesives.

[0005] (2) Technical solution To achieve the above objectives, the present invention provides the following technical solution: A biodegradable leather and plastic adhesive for preventing bulging, comprising the following components by weight: 70-88 parts of epoxy-terminated polyurethane emulsion, which is synthesized from polyester polyol or aliphatic polycarbonate polyol and isophorone diisocyanate, wherein the polyester polyol is selected from polycaprolactone diol or polybutylene adipate diol, and the aliphatic polycarbonate polyol has a number average molecular weight of 1000-3000, and is modified by 2,3-epoxy-1-propanol end-capping, with an end-group density of 0.020-0.100 mmol / g; A fluorine-free polar modified epoxy compound dispersion of 0.8-2.5 parts is prepared by partially ring-opening modification reaction of one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized methyl oleate, or fatty alcohol glycidyl ether with lactic acid, glycolic acid, ethylene glycol, neopentyl glycol, or trimethylolpropane in the presence of a preparative catalyst. The fluorine-free polar modified epoxy compound has an epoxy equivalent of 320-520 g / eq, and the dispersion has a solid content of 30-60 wt%. 7-14 parts of starch acetate with a degree of substitution of 1.8-2.6; 0.5-1.2 parts of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 1:1-3:1; 0.3-1.0 parts of cellulose nanocrystals; 0.1-0.5 parts of curing catalyst, wherein the curing catalyst is selected from 2-methylimidazole, 1-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol or N,N-dimethylbenzylamine.

[0006] This invention employs a multi-component synergistic design primarily to enhance the anti-bubbling, adhesive strength, and water resistance of leather and plastic adhesives. An epoxy-terminated polyurethane emulsion serves as the main substrate, forming a molecular framework with excellent flexibility and adhesion through the synthetic reaction of polyester polyols or aliphatic polycarbonate polyols with isophorone diisocyanate. End-capping modification with 2,3-epoxy-1-propanol further enhances the crosslinking reaction capability. The introduction of a fluorine-free polar modified epoxy compound dispersion, through the ring-opening reaction of natural epoxy compounds such as epoxidized soybean oil and epoxidized linseed oil with polar modifiers such as lactic acid and glycolic acid, significantly improves the polarity and interfacial compatibility of the adhesive while maintaining its environmentally friendly properties. Starch acetate with controllable substitution degree not only imparts good biodegradability to the adhesive but also provides additional hydrogen bonding forces through its unique molecular structure. A silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane can form chemical bonds with the substrate surface, significantly improving the interfacial bonding strength. Cellulose nanocrystals, as a nano-reinforcing phase, play a dual role in stress dispersion and interfacial reinforcement in the cross-linked network through their high aspect ratio and surface-active groups. The components interact through multiple mechanisms, including chemical cross-linking, hydrogen bonding, and physical entanglement, constructing a dense and stable three-dimensional network structure, achieving a comprehensive improvement in anti-blistering properties, high-strength adhesion, and excellent water resistance.

[0007] Furthermore, the preparation method of the epoxy-terminated polyurethane emulsion includes: A1) Prepolymerization step: At 78-82℃, polyester polyol or aliphatic polycarbonate polyol is reacted with isophorone diisocyanate at a molar ratio of 1:1.6-2.4 for 2-4 hours. During the reaction, 2.5-9wt% of 2,2-dimethylolpropionic acid is added, and 90-95mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer. A2) End-group sealing and emulsification chain extension steps: Cool the prepolymer to 48-58℃, add 1.8-3.0wt% of 2,3-epoxy-1-propanol by mass of the prepolymer for end-group sealing reaction for 1.2-2.5h, so that the end-group density reaches 0.020-0.100mmol / g and the residual NCO content is 0.30-0.60wt%, then dilute with water at 20-40℃ to a solid content of 40-60wt%, add 0.3-1.5wt% of compound emulsifier by mass of system, and extend the chain with ethylenediamine or hexamethylenediamine until the residual NCO content is no more than 0.08wt%, and control the final solid content to 48-55wt%.

[0008] Furthermore, the compound emulsifier is a mixture of anionic and nonionic surfactants in a mass ratio of 1:1 to 3:1, wherein the anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol sulfate, and the nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and sorbitan fatty acid ester.

[0009] This invention employs a stepwise reaction process primarily designed to enhance the molecular structure control and crosslinking properties of epoxy-terminated polyurethane emulsions. The prepolymerization step, through precise control of the reaction between polyester polyols or aliphatic polycarbonate polyols and isophorone diisocyanate, combined with the introduction of 2,2-dimethylolpropionic acid and triethylamine, achieves the controllable construction of the polyurethane backbone and the formation of a stable ionized structure. The end-group sealing and emulsification chain extension steps demonstrate the synergistic integration of multiple functions. The 2,3-epoxy-1-propanol end-capping reaction eliminates the reactivity of residual isocyanate while introducing epoxy groups, providing active sites for subsequent crosslinking. The chain extension reaction of ethylenediamine or hexamethylenediamine significantly enhances the hydrogen bonding forces between molecular chains by forming stable urea bond structures. The entire preparation process, through temperature gradient control, stepwise feeding, and monitoring of residual groups, achieves precise regulation of molecular weight distribution and optimization of emulsion stability. This ensures that the final product maintains good flowability while possessing excellent crosslinking reactivity and interfacial adhesion, laying a solid molecular foundation for improving the overall performance of adhesives.

[0010] Furthermore, the preparation method of the fluorine-free polar modified epoxy compound dispersion includes: B1) Modification reaction step: One or more of epoxidized soybean oil, epoxidized linseed oil, and epoxidized methyl oleate, or fatty alcohol glycidyl ether, are reacted with a polar modifier in the presence of a catalyst accounting for 0.1-0.5 wt% of the total mass of the reactants at 35-55℃ for 2.0-5.0 h. The polar modifier is selected from lactic acid, glycolic acid, ethylene glycol, neopentyl glycol, or trimethylolpropane. The molar ratio of hydrophobic groups to polar groups is controlled at 8:1-12:1 so that the epoxy equivalent of the reaction product reaches 320-520 g / eq. The catalyst is selected from 2-methylimidazole, 1-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol, or N,N-dimethylbenzylamine. B2) Mechanical dispersion and stabilization steps: Disperse the mixture at 6000-15000 r / min for 8-35 min using a high-shear disperser, while adding 5-15 wt% of a compound emulsifier aqueous solution to form a stable emulsion with a particle size D50 of 100-280 nm. Then, allow it to stand and mature at 15-30℃ to control the particle size D90 below 450 nm, finally obtaining a stable fluorine-free polar modified epoxy compound dispersion.

[0011] Furthermore, the compound emulsifier is a mixture of anionic and nonionic surfactants in a mass ratio of 1:1 to 2:1, wherein the anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol sulfate, and the nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and sorbitan fatty acid ester.

[0012] This invention employs a preparation design combining controlled modification reactions and mechanical dispersion, primarily aimed at enhancing the interfacial compatibility and dispersion stability of fluorine-free polar modified epoxy compound dispersions. The modification reaction step involves the precise proportioning of epoxidized soybean oil, epoxidized linseed oil, epoxidized methyl oleate, or fatty alcohol glycidyl ether with polar modifiers such as lactic acid, glycolic acid, ethylene glycol, neopentyl glycol, or trimethylolpropane. Under the action of a catalyst, a balanced construction of hydrophobic and polar groups is achieved, maintaining the environmentally friendly characteristics of natural epoxy compounds while significantly improving compatibility with polyurethane matrices. The mechanical dispersion and stabilization steps utilize the synergistic effect of high-shear dispersion technology and compounded emulsifiers to achieve nanoscale uniform dispersion of the modified epoxy compounds. Static curing further optimizes particle size distribution and interfacial stability. The entire preparation process, through dual regulation of chemical modification and physical dispersion, enables the modified epoxy compound to maintain an appropriate epoxy equivalent while possessing excellent water dispersibility and interfacial activity, providing technical support for its multiple functions in adhesive systems, such as enhancing interfacial bonding, improving water resistance, and improving anti-blistering performance.

[0013] Furthermore, in step B1, the fatty alcohol glycidyl ether is lauryl glycidyl ether or glycidyl hexadecyl ether.

[0014] Furthermore, step A1 also includes a metal catalyst, which is a tin-free system, selected from one or more of bismuth neodecanoate, zinc laurate, calcium carboxylate, and magnesium carboxylate, and is used in an amount of 0.005-0.08 wt% of the total monomer mass; Furthermore, the polar modifier described in step B1 has a hydroxyl value of 120-350 mgKOH / g, a reaction temperature of 38-52℃, and a reaction time of 2.5-6h.

[0015] Furthermore, the cross-linked network formed after the adhesive cures has an interfacial bonding strength ≥12 MPa and a water vapor permeability of [missing information]. Water absorption rate ≤4.0wt%.

[0016] This invention also discloses a method for preparing a biodegradable leather-plastic adhesive to prevent bulging, comprising the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals were prepared into an aqueous dispersion with a concentration of 2.0-3.0 wt% at 20-35℃ and dispersed at 250-350W for 12-20 min. Pre-coupling was performed with γ-aminopropyltriethoxysilane accounting for 30-50% of the total silane complex at pH 4.5-5.5. Then, epoxy-terminated polyurethane emulsion was added and stirred for 25-40 min. S2) Addition of fluorine-free components: Add the fluorine-free polar modified epoxy compound dispersion dropwise over 10-20 min at a rate of 0.8-2.5 wt% of the main system, while stirring at 180-450 r / min for 12-25 min. S3) Mixing and homogenization: Add starch acetate and stir at 200-300 r / min for 8-15 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 70-80℃ and hold for 25-60 min. Add 0.1-0.5 wt% of curing catalyst to control the epoxy group to active hydrogen equivalent ratio to be 0.90-1.10. S5) Post-treatment: Cool to 30-45℃, add the remaining silane compound after pre-hydrolyzing at pH 4.5-5.5 for 30-60 minutes, adjust the pH to 7.0-8.0, and perform degassing and maturation to obtain the finished product.

[0017] Furthermore, in step S4, the equivalence ratio of epoxy groups to active hydrogen is 0.90-1.00, the total holding time is 45-90 min, and the viscosity increase rate of the system is 150-250%.

[0018] Application of a biodegradable leather-plastic adhesive that prevents bulging in the bonding of leather and plastic.

[0019] This invention employs a step-by-step crosslinking network construction design primarily to enhance the interfacial bonding strength, water-blocking properties, and crosslinking curing effect of anti-bubbling biodegradable leather-plastic adhesives. The cellulose pretreatment step uses ultrasonic dispersion technology to prepare a uniform aqueous dispersion of cellulose nanocrystals, followed by pre-coupling treatment with γ-aminopropyltriethoxysilane to form a silanized modification layer on the cellulose surface, significantly improving its interfacial compatibility and dispersion stability with the polyurethane matrix. The fluorine-free component addition step ensures uniform distribution of the fluorine-free polar modified epoxy compound dispersion in the system by controlling the dropping rate and stirring intensity, providing sufficient active sites for subsequent crosslinking reactions. The addition of starch acetate during mixing and homogenization not only imparts good biodegradability to the system but also improves the toughness of the cured film through the flexibility of its molecular chains. The crosslinking curing step uses gradient heating and precise control of the epoxy group to active hydrogen equivalent ratio to achieve an optimized balance of crosslinking density, ensuring sufficient crosslinking degree to obtain excellent interfacial bonding strength and low water vapor permeability while avoiding brittleness caused by excessive crosslinking. The post-processing stage further improves the cross-linking network structure through the pre-hydrolysis of silane complex and pH adjustment, so that the final product can achieve an organic unity of environmentally friendly degradation characteristics and high-performance adhesion while possessing excellent anti-bubbling performance.

[0020] (3) Beneficial technical effects 1. Significantly improves interfacial bonding strength and anti-bulging performance: Through the synergistic design of epoxy end-group polyurethane emulsion and fluorine-free polar modified epoxy compound dispersion, combined with the interfacial coupling effect of silane complex and the reinforcing effect of cellulose nanocrystals, a dense and stable three-dimensional cross-linked network structure is constructed, achieving an interfacial bonding strength of over 12 MPa, effectively solving the technical problems of insufficient bonding strength and easy bulging of traditional adhesives.

[0021] 2. Excellent water-blocking performance and water resistance stability: By precisely controlling the equivalent ratio of epoxy groups to active hydrogen and optimizing the crosslinking density, the formed crosslinked network exhibits good density and hydrophobic properties, with water vapor permeability controlled within a certain range. The water absorption rate is below 4.0 wt%, which significantly improves the stability and durability of the adhesive in humid environments.

[0022] 3. Excellent environmental degradation properties: By introducing starch acetate with controllable substitution degree and components such as naturally derived epoxidized soybean oil and epoxidized linseed oil, the adhesive is endowed with good biodegradability while maintaining high-performance bonding, meeting environmental protection requirements and providing a technical path for the development of green adhesives.

[0023] 4. Optimized processing performance: Through the step-by-step construction of the cross-linked network preparation process design, the viscosity growth rate of the system and the adjustability of the curing process are achieved, which not only ensures the applicability and ease of operation of the adhesive, but also ensures the consistency and stability of the final product performance. Attached Figure Description

[0024] Figure 1 These are the infrared Fourier transform (FTIR) spectra of the prepolymerized products from different time periods of this invention.

[0025] Figure 2 The image shows the infrared Fourier transform (FTIR) spectrum of the end-group blocked and emulsified chain-extended products of this invention.

[0026] Figure 3 This invention relates to the effect of end group density on shear strength and water retention rate.

[0027] Figure 4 This invention relates to the effect of epoxy equivalent on shear strength and water resistance retention.

[0028] Figure 5 This invention relates to the effect of the degree of substitution on shear strength and water retention rate. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Example

[0030] A biodegradable leather and plastic adhesive for preventing blistering comprises the following components by weight: 79 parts of epoxy-terminated polyurethane emulsion, which is synthesized from polycaprolactone diol and isophorone diisocyanate and modified by end-capping with 2,3-epoxy-1-propanol, with an end-group density of 0.060 mmol / g; 1.5 parts of a fluorine-free polar modified epoxy compound dispersion, which is prepared by partially ring-opening modification of epoxidized soybean oil with ethylene glycol under the action of a preparation catalyst. In this embodiment, the epoxy equivalent of the fluorine-free polar modified epoxy compound is 420 g / eq, and the solid content of the dispersion is 45 wt%; 10 parts of starch acetate with a degree of substitution of 2.2; 0.8 parts of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 2:1; 0.6 parts of cellulose nanocrystals; and 0.3 parts of a curing catalyst, wherein the curing catalyst in this embodiment is 2-methylimidazole.

[0031] The preparation method of the epoxy-terminated polyurethane emulsion in this embodiment includes: A1) Prepolymerization step: Polycaprolactone diol and isophorone diisocyanate are reacted at 80°C with a molar ratio of 1:2.0 for 3 hours. During the reaction, 2,2-dimethylolpropionic acid accounting for 5.5 wt% of the total monomer mass is added, and 92 mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer; A2) End-group blocking and emulsification chain extension step: The prepolymer of this embodiment is cooled to 53°C, and 2,3-epoxy-1-propanol accounting for 2.4 wt% of the prepolymer mass is added for end-group blocking reaction for 1.8 hours to make the end-group density reach 0.060 mmol / g and the residual NCO content 0.45 wt%. Then, water is added at 30°C to dilute to a solid content of 50 wt%, and a compound emulsifier accounting for 0.9 wt% of the system mass is added. Ethylenediamine is used to extend the chain to a residual NCO content of 0.05 wt%, and the final solid content is controlled to be 51 wt%. The compound emulsifier in this embodiment is a mixture of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1.

[0032] The preparation method of the fluorine-free polar modified epoxy compound dispersion in this embodiment includes: B1) Modification reaction step: Epoxidized soybean oil and a polar modifier are reacted at 45°C for 3.5 h in the presence of a catalyst accounting for 0.3 wt% of the total mass of the reactants. Ethylene glycol is selected as the polar modifier, and the molar ratio of hydrophobic groups to polar groups is controlled at 10:1 to achieve an epoxy equivalent of 420 g / eq in the reaction product. 2-Methylimidazole is selected as the catalyst in this embodiment. B2) Mechanical dispersion and stabilization step: The dispersion is carried out at 10000 r / min for 20 min using a high-shear disperser, while 8 wt% of a compound emulsifier aqueous solution is added to form a stable emulsion with a particle size D50 of 190 nm. The emulsion is then allowed to stand at 22°C for maturation to control the particle size D90 at 420 nm, ultimately obtaining a stable fluorine-free polar modified epoxy compound dispersion. The compound emulsifier in this embodiment is a mixture of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether at a mass ratio of 1:1.

[0033] Step A1 also includes a metal catalyst. In this embodiment, the metal catalyst is a tin-free system, specifically bismuth neodecanoate, used at 0.04 wt% of the total monomer mass. In step B1, the polar modifier in this embodiment has a hydroxyl value of 235 mgKOH / g, a reaction temperature of 45°C, and a reaction time of 3.5 h. The cross-linked network formed after curing of this adhesive has an interfacial bonding strength of 15 MPa and a water vapor permeability of [missing information]. The water absorption rate is 3.2 wt%.

[0034] The preparation method of the anti-bulging biodegradable leather and plastic adhesive in this embodiment includes the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals are prepared into an aqueous dispersion with a concentration of 2.5 wt% at 27°C, dispersed at 300W power for 16 min, pre-coupled with γ-aminopropyltriethoxysilane accounting for 40% of the total silane complex at pH 5.0, and then epoxy-terminated polyurethane emulsion is added and stirred for 32 min; S2) Addition of fluorine-free components: The fluorine-free polar modified epoxy compound dispersion is added dropwise over 15 min at a mass of 1.5 wt% of the main system. Simultaneously, stir at 315 r / min for 18 min; S3) Mixing and homogenization: Add starch acetate and stir at 250 r / min for 12 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 75℃ and hold for 42 min, add 0.3 wt% of curing catalyst, and control the epoxy group to active hydrogen equivalent ratio to be 1.00; S5) Post-treatment: Cool down to 37℃, add the remaining silane complex after pre-hydrolyzing at pH 5.0 for 45 min, adjust the pH to 7.5, and perform degassing and curing to obtain the finished product.

[0035] In step S4, the equivalent ratio of epoxy groups to active hydrogen is 0.95, the total holding time is 67 min, and the viscosity growth rate of the system is 200%.

[0036] This embodiment uses a moderate parameter configuration, which achieves a good balance of comprehensive performance while ensuring product stability. The moderate design of end group density and epoxy equivalent ensures a moderate crosslinking density, which is suitable for conventional leather-plastic composite bonding applications that require both adhesive strength and flexibility. Example

[0037] A biodegradable leather-plastic adhesive for preventing bulging comprises the following components by weight: 85 parts of an epoxy-terminated polyurethane emulsion, which is synthesized from an aliphatic polycarbonate polyol and isophorone diisocyanate. In this embodiment, the aliphatic polycarbonate polyol has a number average molecular weight of 2500 and is end-capped with 2,3-epoxy-1-propanol, resulting in an end-group density of 0.035 mmol / g; and 1.0 part of a fluorine-free polar modified epoxy compound dispersion, which is prepared by partially ring-opening modification of neopentyl glycol with a mixture of epoxidized linseed oil and epoxidized methyl oleate at a mass ratio of 60 wt% and 40 wt% under the action of a preparation catalyst. In this embodiment, the epoxy equivalent of the fluorine-free polar modified epoxy compound is 380. g / eq, the solid content of the dispersion in this embodiment is 55wt%; 8 parts of starch acetate with a degree of substitution of 1.9; 1.0 part of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 1.5:1; 0.4 parts of cellulose nanocrystals; 0.2 parts of curing catalyst, the curing catalyst in this embodiment is 1-methylimidazole.

[0038] The preparation method of the epoxy-terminated polyurethane emulsion in this embodiment includes: A1) Prepolymerization step: Aliphatic polycarbonate polyol and isophorone diisocyanate are reacted at 79°C with a molar ratio of 1:1.8 for 2.5 h. During the reaction, 2,2-dimethylolpropionic acid accounting for 3.5 wt% of the total monomer mass is added, and 93 mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer; A2) End-group blocking and emulsification chain extension step: The prepolymer of this embodiment is cooled to 50°C, and 2,3-epoxy-1-propanol accounting for 2.0 wt% of the prepolymer mass is added for end-group blocking reaction for 1.5 h to make the end-group density reach 0.035 mmol / g and the residual NCO content 0.35 wt%. Then, water is added at 25°C to dilute to a solid content of 45 wt%, and a compound emulsifier accounting for 0.6 wt% of the system mass is added. Hexamethylenediamine is used for chain extension to make the residual NCO content 0.06 wt%, and the final solid content is controlled to be 52 wt%. The compound emulsifier in this embodiment is a mixture of sodium dodecylbenzenesulfonate and nonylphenol polyoxyethylene ether in a mass ratio of 2.5:1.

[0039] The preparation method of the fluorine-free polar modified epoxy compound dispersion in this embodiment includes: B1) Modification reaction step: Epoxy linseed oil and epoxidized methyl oleate are mixed at a mass ratio of 60wt% and 40wt% respectively, and a polar modifier is prepared in the presence of a catalyst accounting for 0.2wt% of the total mass of the reactants. The mixture is reacted at 40°C for 4.0h. The polar modifier is neopentyl glycol, and the molar ratio of hydrophobic groups to polar groups is controlled at 9:1 so that the epoxy equivalent of the reaction product reaches 380 g / eq. The preparation catalyst in this embodiment is 1-methylimidazole; B2) Mechanical dispersion and stabilization treatment step: The mixture is dispersed at 8000r / min for 15min using a high shear disperser, and 5wt% of a compound emulsifier aqueous solution is added at the same time to form a stable emulsion with a particle size D50 of 150nm. Then, the mixture is allowed to stand and mature at 18°C ​​to control the particle size D90 at 380nm, and finally a stable fluorine-free polar modified epoxy compound dispersion is obtained. The compound emulsifier in this embodiment is a mixture of sodium dodecylbenzenesulfonate and nonylphenol polyoxyethylene ether in a mass ratio of 2:1.

[0040] Step A1 also includes a metal catalyst. In this embodiment, the metal catalyst is a tin-free system, using a mixture of zinc laurate and calcium carboxylate at a mass ratio of 70wt% and 30wt%, respectively, with an amount of 0.02wt% of the total monomer mass. In step B1, the polar modifier in this embodiment has a hydroxyl value of 180 mgKOH / g, a reaction temperature of 40℃, and a reaction time of 4.0 h. The cross-linked network formed after curing of this adhesive has an interfacial bonding strength of 13 MPa and a water vapor permeability of... The water absorption rate is 2.8 wt%.

[0041] The preparation method of the anti-bulging biodegradable leather and plastic adhesive in this embodiment includes the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals are prepared into an aqueous dispersion with a concentration of 2.2 wt% at 23°C, dispersed at 275W power for 14 min, pre-coupled with γ-aminopropyltriethoxysilane accounting for 35% of the total silane complex at pH 4.8, and then epoxy-terminated polyurethane emulsion is added and stirred for 28 min; S2) Addition of fluorine-free components: The fluorine-free polar modified epoxy compound dispersion is added dropwise over 12 min at a concentration of 1.0 wt% of the main system. Simultaneously, stir at 250 r / min for 15 min; S3) Mixing and homogenization: Add starch acetate and stir at 220 r / min for 10 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 72℃ and hold for 35 min, add 0.2 wt% of curing catalyst, and control the epoxy group to active hydrogen equivalent ratio to be 0.95; S5) Post-treatment: Cool down to 33℃, add the remaining silane compound after pre-hydrolyzing at pH 4.8 for 35 min, adjust the pH to 7.2, and perform degassing and curing to obtain the finished product.

[0042] In step S4, the equivalence ratio of epoxy groups to active hydrogen is 0.92, the total holding time is 55 min, and the viscosity increase rate of the system is 175%.

[0043] This embodiment focuses on optimizing flexibility and low-temperature performance. It adopts a high molecular weight aliphatic polycarbonate polyol and a low end group density design, and the resulting crosslinked network has good flexibility and impact resistance. It is particularly suitable for bonding applications of automotive interior leather plastic composite materials that need to withstand mechanical stress deformation. Example

[0044] A biodegradable leather-plastic adhesive for preventing bulging comprises, by weight, the following components: 72 parts of an epoxy-terminated polyurethane emulsion, which is synthesized from polybutylene adipate diol and isophorone diisocyanate and modified by 2,3-epoxy-1-propanol end-capping, with an end-group density of 0.085 mmol / g; and 2.3 parts of a fluorine-free polar modified epoxy compound dispersion, which is prepared by partially ring-opening modification of lauryl glycidyl ether with trimethylolpropane in the presence of a preparative catalyst. In this embodiment, the epoxy equivalent of the fluorine-free polar modified epoxy compound is 480. g / eq, the solid content of the dispersion in this embodiment is 35wt%; 13 parts of starch acetate with a degree of substitution of 2.5; 1.1 parts of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 2.5:1; 0.9 parts of cellulose nanocrystals; 0.4 parts of curing catalyst, the curing catalyst in this embodiment is 2,4,6-tris(dimethylaminomethyl)phenol.

[0045] The preparation method of the epoxy-terminated polyurethane emulsion in this embodiment includes: A1) Prepolymerization step: Polybutylene adipate diol and isophorone diisocyanate are reacted at 81°C with a molar ratio of 1:2.2 for 3.5 h. During the reaction, 7.5 wt% of 2,2-dimethylolpropionic acid is added, and 94 mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer; A2) End-group blocking and emulsification chain extension step: The prepolymer of this embodiment is cooled to 55°C, and 2.8 wt% of 2,3-epoxy-1-propanol is added for end-group blocking reaction for 2.2 h to achieve an end-group density of 0.085. The sample was prepared with a solid content of 0.55 wt% NCO and a residual NCO content of mmol / g. It was then diluted with water at 35°C to a solid content of 42 wt%. A compound emulsifier (1.3 wt% by mass) was added, and the chain was extended with ethylenediamine until the residual NCO content was 0.04 wt%, controlling the final solid content to 49 wt%. In this embodiment, the compound emulsifier was a mixture of sodium fatty alcohol sulfate and nonylphenol polyoxyethylene ether in a 1:1 mass ratio.

[0046] The preparation method of the fluorine-free polar modified epoxy compound dispersion in this embodiment includes: B1) Modification reaction step: lauryl glycidyl ether and a polar modifier are reacted at 50°C for 2.8 h in the presence of a catalyst accounting for 0.4 wt% of the total mass of the reactants. The polar modifier is trimethylolpropane, and the molar ratio of hydrophobic groups to polar groups is controlled at 11:1 so that the epoxy equivalent of the reaction product reaches 480 g / eq. The catalyst used in this embodiment is 2,4,6-tris(dimethylaminomethyl)phenol; B2) Mechanical dispersion and stabilization treatment step: dispersion is carried out at 12000 r / min for 28 min using a high shear disperser, while 5-15 wt% of a compound emulsifier aqueous solution is added to form a stable emulsion with a particle size D50 of 240 nm. Then, it is allowed to stand and mature at 25°C to control the particle size D90 at 440 nm, and finally a stable fluorine-free polar modified epoxy compound dispersion is obtained. The compound emulsifier in this embodiment is a mixture of sodium fatty alcohol sulfate and nonylphenol polyoxyethylene ether in a mass ratio of 1:1.

[0047] Step A1 also includes a metal catalyst. In this embodiment, the metal catalyst is a tin-free system, using magnesium carboxylate at a dosage of 0.06 wt% of the total monomer mass. In step B1, the polar modifier in this embodiment has a hydroxyl value of 320 mgKOH / g, a reaction temperature of 50°C, and a reaction time of 2.8 h. The cross-linked network formed after curing of this adhesive has an interfacial bonding strength of 18 MPa and a water vapor permeability of [missing information]. The water absorption rate is 3.8 wt%.

[0048] The preparation method of the anti-bulging biodegradable leather and plastic adhesive of this embodiment includes the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals are prepared into an aqueous dispersion with a concentration of 2.8wt% at 32°C, dispersed at 340W power for 18min, pre-coupled with γ-aminopropyltriethoxysilane accounting for 45% of the total silane complex at pH 5.2, and then epoxy-terminated polyurethane emulsion is added and stirred for 37min; S2) Addition of fluorine-free components: The fluorine-free polar modified epoxy compound dispersion is added dropwise over 18min at a mass of 2.3wt% of the main system. Simultaneously, stir at 380 r / min for 22 min; S3) Mixing and homogenization: Add starch acetate and stir at 280 r / min for 13 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 78℃ and hold for 50 min, add 0.4 wt% of curing catalyst, and control the epoxy group to active hydrogen equivalent ratio to be 1.05; S5) Post-treatment: Cool down to 42℃, add the remaining silane complex after pre-hydrolyzing at pH 5.2 for 50 min, adjust the pH to 7.8, and perform degassing and curing to obtain the finished product.

[0049] In step S4, the equivalent ratio of epoxy groups to active hydrogen is 0.98, the total holding time is 70 min, and the viscosity growth rate of the system is 230%.

[0050] This embodiment emphasizes high crosslinking density and excellent interfacial bonding performance. By designing a high end group density and catalyst dosage, a dense crosslinking network structure is formed, which significantly improves the bonding strength and water resistance. It is particularly suitable for bonding applications of leather and plastic composite materials in outdoor sports products with high strength requirements. Example

[0051] A biodegradable leather-plastic adhesive for preventing bulging comprises the following components by weight: 70 parts of epoxy-terminated polyurethane emulsion, which is synthesized from aliphatic polycarbonate polyol and isophorone diisocyanate. In this embodiment, the aliphatic polycarbonate polyol has a number average molecular weight of 1200 and is end-capped with 2,3-epoxy-1-propanol, with an end-group density of 0.095 mmol / g; and 2.5 parts of a fluorine-free polar modified epoxy compound dispersion, which is prepared by partially ring-opening modification of epoxidized soybean oil and glycidyl hexadecyl ether mixed at a mass ratio of 50 wt% and 50 wt% with a catalyst and then reacted with glycolic acid. In this embodiment, the epoxy equivalent of the fluorine-free polar modified epoxy compound is 350. g / eq, the solid content of the dispersion in this embodiment is 60wt%; 14 parts of starch acetate with a degree of substitution of 1.8; 1.2 parts of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 3:1; 1.0 part of cellulose nanocrystals; 0.5 parts of curing catalyst, the curing catalyst in this embodiment is N,N-dimethylbenzylamine.

[0052] The preparation method of the epoxy-terminated polyurethane emulsion in this embodiment includes: A1) Prepolymerization step: Aliphatic polycarbonate polyol and isophorone diisocyanate are reacted at 82°C with a molar ratio of 1:2.4 for 2 hours. During the reaction, 2,2-dimethylolpropionic acid accounting for 8.5 wt% of the total monomer mass is added, and 95 mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer; A2) End-group blocking and emulsification chain extension step: The prepolymer of this embodiment is cooled to 48°C, and 2,3-epoxy-1-propanol accounting for 3.0 wt% of the prepolymer mass is added for end-group blocking reaction for 2.5 hours to make the end-group density reach 0.095 mmol / g and the residual NCO content 0.60 wt%. Then, water is added at 20°C to dilute to a solid content of 40 wt%, and a compound emulsifier accounting for 1.5 wt% of the system mass is added. Hexamethylenediamine is used for chain extension to make the residual NCO content 0.08 wt%, and the final solid content is controlled to be 48 wt%. The compound emulsifier in this embodiment is a mixture of sodium dodecyl sulfate and sorbitan fatty acid ester in a mass ratio of 2:1.

[0053] The preparation method of the fluorine-free polar modified epoxy compound dispersion in this embodiment includes: B1) Modification reaction step: Epoxidized soybean oil and glycidyl hexadecyl ether are mixed at a mass ratio of 50wt% and 50wt% respectively, and a polar modifier is prepared in the presence of a catalyst accounting for 0.5wt% of the total mass of the reactants. The mixture is reacted at 52°C for 2.5h. The polar modifier is glycolic acid, and the molar ratio of hydrophobic groups to polar groups is controlled at 8:1 so that the epoxy equivalent of the reaction product reaches 350 g / eq. The preparation catalyst in this embodiment is N,N-dimethylbenzylamine; B2) Mechanical dispersion and stabilization treatment step: The mixture is dispersed at 14000r / min for 32min using a high-shear disperser, and 5-15wt% of a compound emulsifier aqueous solution is added at the same time to form a stable emulsion with a particle size D50 of 120nm. Then, the mixture is allowed to stand and mature at 28°C to control the particle size D90 at 350nm, and finally a stable fluorine-free polar modified epoxy compound dispersion is obtained. The compound emulsifier in this embodiment is a mixture of sodium dodecyl sulfate and sorbitan fatty acid ester in a mass ratio of 2:1.

[0054] Step A1 also includes a metal catalyst. In this embodiment, the metal catalyst is a tin-free system, using a mixture of bismuth neodecanoate and zinc laurate at a mass ratio of 40wt% and 60wt%, respectively, with an amount of 0.075wt% of the total monomer mass. In step B1, the polar modifier in this embodiment has a hydroxyl value of 140 mgKOH / g, a reaction temperature of 52℃, and a reaction time of 2.5h. The cross-linked network formed after curing of this adhesive has an interfacial bonding strength of 20 MPa and a water vapor permeability of... The water absorption rate is 3.5 wt%.

[0055] The preparation method of the anti-bulging biodegradable leather and plastic adhesive in this embodiment includes the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals are prepared into an aqueous dispersion with a concentration of 3.0 wt% at 35°C, dispersed at 350W power for 20 min, pre-coupled with γ-aminopropyltriethoxysilane accounting for 50% of the total silane complex at pH 5.5, and then epoxy-terminated polyurethane emulsion is added and stirred for 40 min; S2) Addition of fluorine-free components: The fluorine-free polar modified epoxy compound dispersion is added dropwise over 10 min at a mass of 2.5 wt% of the main system. Simultaneously, stir at 450 r / min for 25 min; S3) Mixing and homogenization: Add starch acetate and stir at 300 r / min for 15 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 80℃ and hold for 60 min, add 0.5 wt% of curing catalyst, and control the epoxy group to active hydrogen equivalent ratio to be 1.10; S5) Post-treatment: Cool down to 45℃, add the remaining silane compound after pre-hydrolyzing at pH 5.5 for 60 min, adjust the pH to 8.0, and perform degassing and curing to obtain the finished product.

[0056] In step S4, the equivalent ratio of epoxy groups to active hydrogen is 1.00, the total holding time is 80 min, and the viscosity growth rate of the system is 250%.

[0057] This embodiment aims for high crosslinking density and maximized biodegradability. It employs a higher starch acetate content and a high-end base density design to achieve rapid crosslinking and curing, as well as excellent environmental degradation characteristics, while maintaining outstanding overall performance. It is particularly suitable for green packaging and sustainable leather product bonding applications with extremely high environmental protection requirements.

[0058] Comparative Example 1: It is basically the same as Example 1, except that the end group density in step A2 is 0.015 mmol / g, which is obtained by reducing the amount of 2,3-epoxy-1-propanol to 1.0 wt% of the prepolymer mass and extending the end-capping reaction time to 2.8 h.

[0059] Comparative Example 2: It is basically the same as Example 1, except that the epoxy equivalent of the fluorine-free polar modified epoxy compound in step B1 is 580 g / eq, which is obtained by reducing the modification reaction temperature to 30°C and reducing the reaction time to 2.0 h.

[0060] Comparative Example 3: It is basically the same as Example 1, except that the solid content of the dispersion in step B2 is 25 wt%, which is obtained by increasing the amount of compound emulsifier aqueous solution by 5-15 wt% and extending the high shear dispersion time to 35 min.

[0061] Comparative Example 4: It is basically the same as Example 1, except that the degree of substitution of starch acetate is 1.2. This starch acetate is prepared by reacting starch with acetic anhydride at 60°C for 1.5 h, and controlling the molar ratio of acetic anhydride to starch hydroxyl groups to be 0.8:1.

[0062] Comparative Example 5: It is basically the same as Example 1, except that the silane complex is composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 0.5:1.

[0063] Comparative Example 6: It is basically the same as Example 1, except that the curing catalyst used is triethylamine, and the amount is 0.3 parts.

[0064] Comparative Example 7: Basically the same as Example 1, except that the prepolymerization reaction temperature in step A1 is 95°C and the reaction time is 3h.

[0065] Comparative Example 8: Basically the same as Example 1, except that in step A1, polycaprolactone diol and isophorone diisocyanate react in a molar ratio of 1:1.2.

[0066] Comparative Example 9: Basically the same as Example 1, except that in step A1, 2,2-dimethylolpropionic acid accounts for 12 wt% of the total monomer mass, and triethylamine neutralizes 92 mol% of the carboxyl groups.

[0067] Comparative Example 10: It is basically the same as Example 1, except that in step A2 the prepolymer is cooled to 35°C for end-group blocking reaction, and the end-group blocking reaction time is 0.8h.

[0068] Comparative Example 11: Basically the same as Example 1, except that the modification reaction temperature in step B1 is 65°C and the reaction time is 3.5h.

[0069] Comparative Example 12: Basically the same as Example 1, except that the molar ratio of hydrophobic groups to polar groups in step B1 is 15:1, which is obtained by reducing the amount of ethylene glycol.

[0070] Comparative Example 13: Basically the same as Example 1, except that in step B2 the high shear disperser speed is 4000 r / min and the dispersion time is 20 min.

[0071] Comparative Example 14: Basically the same as Example 1, except that the dispersion power of cellulose nanocrystals in step S1 is 150W and the dispersion time is 16min.

[0072] Performance testing: Adhesive Viscosity Performance Test: The test object is the rheological properties of a biodegradable leather / plastic adhesive in its liquid state to prevent blistering. The purpose of the test is to evaluate the adhesive's workability and flowability. The test principle is based on the flow behavior of Newtonian or non-Newtonian fluids under shear stress. The experimental method uses a rotational viscometer at 25±1℃, using a No. 2 rotor at 60 rpm to measure the apparent viscosity of the adhesive. The value is read after stabilizing for 30 seconds. The standard is GB / T 2794-2013 "Determination of Viscosity of Adhesives". Key parameters include test temperature 25±1℃, sample volume 500mL, and rotation speed 60 rpm. Data processing: The viscosity value is directly read to determine whether it is within the process requirements and to evaluate the adhesive's workability.

[0073] Shear bond strength test: The test object is the adhesive joint formed at the leather-plastic interface by the anti-bubble biodegradable leather-plastic adhesive. The purpose of the test is to evaluate the basic adhesive performance and interfacial bond strength of the adhesive. The test principle is based on the mechanical response and failure mechanism of the adhesive joint under shear load. Experimental method: 25mm×100mm standard specimens are prepared. The substrates are natural cow leather (1.2mm thick) and PVC artificial leather (surface corona treatment). The adhesive coating thickness is 0.1mm. After curing at 23℃ for 24 hours, a shear test is performed using a universal testing machine at a tensile speed of 5mm / min. The standard is GB / T 7124-2008 "Determination of Tensile Shear Strength of Adhesives". Key parameters include the number of specimens (5), test speed (5mm / min), and curing time (24h). Data processing: The average shear strength is calculated to determine whether the technical requirements are met and to evaluate the bonding quality.

[0074] Anti-bulging performance test: The test object is the anti-bulging ability of the biodegradable leather-plastic adhesive in leather-plastic composite structures. The purpose of the test is to evaluate the performance of the adhesive in preventing interfacial delamination and localized bulging under humid and hot conditions. The test principle is based on the bulging phenomenon caused by the diffusion and accumulation of water vapor in the adhesive layer and the failure of interfacial adhesion under thermal stress. Experimental method: 100mm×100mm leather-adhesive-plastic three-layer composite samples were prepared, kept in a humid heat chamber at 40℃ / 90%RH for 24 hours, and then dried in an oven at 80℃ for 2 hours. The surface bulging was visually inspected. The standard is GB / T 2423.3-2016 "Environmental Testing - Constant Humidity and Heat Test". Key parameters include humid heat temperature of 40℃, relative humidity of 90%, treatment time of 24±2h, and number of samples of 3. Data processing: Bugging level is rated from 0 to 5, with level 0 being no bulging and level 5 being severe bulging, to evaluate the anti-bulging performance of the adhesive.

[0075] Water Resistance Test: The test object is the stability of the bonded joint of the cured anti-blister biodegradable leather-plastic adhesive in a water environment. The purpose of the test is to evaluate the durability of the adhesive in a humid environment. The test principle is based on the influence of water molecules on the polymer network and interfacial bonding. Experimental Method: Standard shear test specimens are completely immersed in distilled water at 23°C for 7 days, then dried under standard conditions for 24 hours before shear strength is tested. The standard is based on Appendix GB / T 7124-2008. Key parameters include immersion temperature 23°C, immersion time 7 days, and number of specimens 5. Data Processing: Strength retention rate is calculated to evaluate the water resistance rating of the adhesive.

[0076] Biodegradability Test: The test subject is the biodegradation behavior of a pure adhesive-cured film of a biodegradable leather-plastic adhesive for preventing blistering in a composting environment. The purpose of the test is to evaluate the environmental friendliness and biodegradability of the adhesive. The test principle is based on the change in CO2 release caused by the enzymatic hydrolysis and mineralization of organic polymers by microorganisms. Experimental Method: Adhesive samples are prepared into small pieces of 2mm × 2mm × 0.5mm and subjected to a 180-day degradation test in a composting environment at 58±2℃ and 58±5% relative humidity. The CO2 release and sample mass changes are measured periodically. Cellulose, PLA (positive control), and PE (negative control) are set up for comparison. Bio-based carbon content (ASTM D6866) and ecotoxicity (OECD 208 / 221) are also tested. Key parameters include composting temperature 58±2℃, pH 7.0-9.0, moisture content 50-60%, sample mass 300-500mg, and test period 180 days. Data processing is used to calculate biodegradation rate, biodegradation rate constant, and half-life to evaluate the biodegradation level and environmental safety of materials.

[0077] The performance of the adhesives in the examples and comparative examples is summarized in Table 1. Comparative Example 1, due to its low end-group density leading to a loose crosslinking network, exhibited a shear strength of only 3.2 MPa and its anti-bulging performance deteriorated to level 3, with a water retention rate decreasing to 65.3%. Comparative Example 2, due to its excessive epoxy equivalent resulting in insufficient crosslinking efficiency, had a shear strength of 4.1 MPa; although its performance improved, it was still significantly lower than the examples. Comparative Example 3, due to its low solid content leading to insufficient effective components, had a shear strength of 4.8 MPa and an anti-bulging performance of level 2, but its biodegradation rate remained at a normal level of 79.1%. Comparative Example 4, due to its low starch acetate substitution, achieved a shear strength of 5.3 MPa and a biodegradation rate as high as 87.3%, but its anti-bulging performance remained at level 1, with a water retention rate of 82.4%. Comparative Examples 5-7 demonstrated the combined effects of various formulation deviations, with shear strengths ranging from 4.6 to 5.8 MPa. Within the MPa range, the anti-bulging performance was grade 1-2, indicating a moderate level of performance. Comparative Example 8, due to a severe imbalance in the NCO:OH ratio leading to insufficient crosslinking, had a shear strength of only 2.8 MPa, resulting in a deterioration of its anti-bulging performance to grade 4 and a water retention rate dropping to 58.2%, making it the worst-performing sample. Comparative Example 9, while achieving a crosslinking strength of 5.4 MPa due to excessive DMPA content, also introduced too many hydrophilic groups, significantly reducing its water retention rate to 68.7%. Comparative Examples 10-14 reflected the influence of process parameters such as insufficient high shear, improper catalyst dosage, and end-group density deviation. They generally exhibited moderate shear strengths of 3.8-5.2 MPa, anti-bulging performance mostly at grade 2, and water retention rates fluctuating between 69-85%. Overall, none of these examples achieved the superior performance of 6.2-8.1 MPa shear strength, grade 0 anti-bulging performance, and 85-91% water retention rate, fully demonstrating the importance and technological advancement of the synergistic optimization of key parameters in this invention.

[0078] Table 1 Summary of the performance of the adhesives in the examples and comparative examples

[0079] based on Figure 1 and Figure 2 The infrared Fourier transform (FTIR) spectra shown can provide the following evidentiary conclusions regarding the rationality, reliability, and effectiveness of the present invention: First, Figure 1The study demonstrates the chemical structural evolution of prepolymerization over time, with the regular changes in characteristic peak positions perfectly matching the expected mechanism: the isocyanate –NCO in the 2275–2250 cm⁻¹ range continuously weakens with increasing prepolymerization time, indicating that –NCO is gradually consumed in the reaction; simultaneously, the absorption of urethane / amide carbonyl groups in the 1720–1700 cm⁻¹ range and urea groups in the 1680–1630 cm⁻¹ range gradually increases, characterizing the formation of newly formed urethane and urea bonds; the ester group C=O (1745–1720 cm⁻¹) and the fingerprint region C–O–C / Si–O–Si (1200–1020 / 1130–1050 cm⁻¹) maintain reasonable relative intensity changes, reflecting the stability and gradual construction of the main chain and side groups; the synergistic changes of the OH broadband (~3400 cm⁻¹) and carboxylic acid-related band positions further confirm the evolution of the degree of neutralization and the hydrogen bonding environment. These spectroscopic pieces of evidence point to the same chemical fact: the prepolymerization reaction proceeds along the designed route, the structure transforms from an ordered monomer / oligomer to the target prepolymer, and the directionality and selectivity of the reaction are supported by both qualitative and semi-quantitative spectroscopic analysis. Secondly, Figure 2 The comparative spectra of the products before and after end-group closure and emulsification chain extension are presented. After end-group closure, the characteristic peaks of epoxy / end-group closure (such as 915±10 cm⁻¹ and 830–840 cm⁻¹) are clearly introduced, while the residual –NCO peak further decreases or even disappears, proving that the end-closing reaction is effectively completed. After emulsification chain extension, the relative absorption of the urea / carbamate carbonyl region (1680–1700 cm⁻¹) is enhanced, and the intensity of the C–O–C and Si–O–Si combination bands in the fingerprint region undergoes a reasonable redistribution, reflecting the chain segment growth and networking trend. At the same time, the characteristic peak of epoxy weakens as expected, indicating that epoxy participates in further reactions and is consumed, and the system evolves towards a higher conversion rate and a more stable structural state. Figure 1 and Figure 2 The appearance, disappearance, and shift intensity changes of the spectral peaks correspond one-to-one with the chemical logic of the reaction steps, and there are no abnormal bands that contradict the mechanism, indicating that the test data are consistent, the signal-to-noise ratio and resolution meet the criteria, and the repeatability and traceability can also be verified by multi-stage sequence comparison. Therefore, it can be proven that the pre-polymerization-end-blocking-emulsification chain extension process of this invention has inherent self-consistency and external verifiability at the spectroscopic level. The directional transformation of key functional groups is clearly recorded by the FTIR characteristic peak sequence, indicating that the scheme is reasonable in achieving the target structure construction; the peak intensity shows a monotonic and interpretable change with the reaction process, indicating that the operation and characterization process is reliable; the end-group regulation and chain extension results are effectively responded to in the functional zones, proving that the technical route is effective in performance and structure regulation. In summary, relying on... Figure 1 and Figure 2 The FTIR evidence chain fully demonstrates the rationality, reliability, and effectiveness of the present invention.

[0080] pass Figure 3-5 The systematic single-factor experimental results fully demonstrate the rationality, reliability and effectiveness of the technical solution of the present invention. Figure 3 The end-group density exhibits a typical inverted U-shaped performance curve in the range of 0.020-0.100 mmol / g, reaching the optimal performance equilibrium point in the range of 0.060-0.070 mmol / g, with a peak shear strength of 6.8-6.9 MPa and the highest water retention rate of 88.5-88.8%. When the end-group density is below 0.020 mmol / g, the loose cross-linking network leads to a sharp deterioration in performance to 3.2-3.9 MPa and 65.3-71.8%, while above 0.100 mmol / g, excessive cross-linking causes the material to become brittle, and the performance decreases to 5.8 MPa and 85.9%, proving the scientific rationality of the technical range setting. Figure 4 This indicates that the epoxy equivalent also exhibits an optimal window effect within the technical range of 320-520 g / eq, reaching its optimal performance near 420 g / eq, with a shear strength of 6.8 MPa and a water resistance retention rate of 88.5%. Below 320 g / eq, excessive active groups lead to increased side reactions and poor processability, while above 520 g / eq, insufficient crosslinking efficiency results in a significant performance drop to 4.1 MPa and 72.1%. The significant performance differences between the technical parameters and those outside the range verify the technological advancement of the parameter selection. Figure 5 This study reveals the performance optimization rules of starch acetate with a substitution degree ranging from 1.8 to 2.6, achieving an optimal hydrophobic-hydrophilic balance around 2.2, with a shear strength of 6.8 MPa and a water resistance retention rate of 88.5%. Too low a substitution degree results in excessive polarity and poor compatibility, leading to suboptimal performance; too high a substitution degree results in excessive hydrophobicity, affecting biodegradability. The optimal values ​​of all three key parameters are located within the technical range and far from the boundary values, forming a stable window of technical advantage. The single-factor experimental data are logically consistent with the performance of the examples and comparative examples, fully demonstrating that the technical solution of this invention achieves a systematic improvement in material performance through multi-parameter synergistic optimization. This provides reliable technical support and theoretical basis for the industrial application of anti-bulging biodegradable leather plastic adhesives.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A biodegradable leather and plastic adhesive for preventing bulging, characterized in that, It includes the following components in parts by weight: 70-88 parts of epoxy-terminated polyurethane emulsion, which is synthesized from polyester polyol or aliphatic polycarbonate polyol and isophorone diisocyanate, wherein the polyester polyol is selected from polycaprolactone diol or polybutylene adipate diol, and the aliphatic polycarbonate polyol has a number average molecular weight of 1000-3000, and is modified by 2,3-epoxy-1-propanol end-capping, with an end-group density of 0.020-0.100 mmol / g; A fluorine-free polar modified epoxy compound dispersion of 0.8-2.5 parts is prepared by partially ring-opening modification reaction of one or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized methyl oleate, or fatty alcohol glycidyl ether with lactic acid, glycolic acid, ethylene glycol, neopentyl glycol, or trimethylolpropane in the presence of a preparative catalyst. The fluorine-free polar modified epoxy compound has an epoxy equivalent of 320-520 g / eq, and the dispersion has a solid content of 30-60 wt%. 7-14 parts of starch acetate with a degree of substitution of 1.8-2.6; 0.5-1.2 parts of a silane complex composed of γ-aminopropyltriethoxysilane and 3-methacryloyloxypropyltrimethoxysilane in a mass ratio of 1:1-3:1; 0.3-1.0 parts of cellulose nanocrystals; 0.1-0.5 parts of curing catalyst, wherein the curing catalyst is selected from 2-methylimidazole, 1-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol or N,N-dimethylbenzylamine.

2. The anti-bulging biodegradable leather and plastic adhesive as described in claim 1, characterized in that, The preparation method of the epoxy-terminated polyurethane emulsion includes: A1) Prepolymerization step: At 78-82℃, polyester polyol or aliphatic polycarbonate polyol is reacted with isophorone diisocyanate at a molar ratio of 1:1.6-2.4 for 2-4 hours. During the reaction, 2.5-9wt% of 2,2-dimethylolpropionic acid is added, and 90-95mol% of the carboxyl groups are neutralized with triethylamine to form a carboxyl-containing prepolymer. A2) End-group sealing and emulsification chain extension step: The prepolymer is cooled to 48-58℃, and 1.8-3.0 wt% of 2,3-epoxy-1-propanol is added to carry out the end-group sealing reaction for 1.2-2.5 h, so that the end-group density reaches 0.020-0.

100. The sample contains mmol / g of residual NCO with a content of 0.30-0.60 wt%. It is then diluted with water at 20-40℃ to a solid content of 40-60 wt%. A compound emulsifier is added at 0.3-1.5 wt% of the system mass. The chain is extended with ethylenediamine or hexamethylenediamine until the residual NCO content is no more than 0.08 wt%, controlling the final solid content to 48-55 wt%. The compound emulsifier is a combination of anionic and nonionic surfactants in a mass ratio of 1:1-3:

1. The anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol sulfate. The nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and sorbitan fatty acid ester.

3. The anti-bulging biodegradable leather and plastic adhesive as described in claim 1, characterized in that, The preparation method of the fluorine-free polar modified epoxy compound dispersion includes: B1) Modification reaction step: One or more of epoxidized soybean oil, epoxidized linseed oil, epoxidized methyl oleate or fatty alcohol glycidyl ether are reacted with a polar modifier in the presence of a catalyst accounting for 0.1-0.5 wt% of the total mass of the reactants at 35-55℃ for 2.0-5.0 h. The polar modifier is selected from lactic acid, glycolic acid, ethylene glycol, neopentyl glycol or trimethylolpropane. The molar ratio of hydrophobic groups to polar groups is controlled at 8:1-12:1 so that the epoxy equivalent of the reaction product reaches 320-520 g / eq. The catalyst is selected from 2-methylimidazole, 1-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol or N,N-dimethylbenzylamine. B2) Mechanical dispersion and stabilization steps: Disperse the mixture at 6000-15000 r / min for 8-35 min using a high-shear disperser, while adding 5-15 wt% of a compound emulsifier aqueous solution to form a stable emulsion with a particle size D50 of 100-280 nm. Then, allow it to stand and mature at 15-30℃ to control the particle size D90 below 450 nm, finally obtaining a stable fluorine-free polar modified epoxy compound dispersion. The compound emulsifier is a mixture of anionic and nonionic surfactants in a mass ratio of 1:1-2:

1. The anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium fatty alcohol sulfate, and the nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and sorbitan fatty acid ester.

4. The anti-bulging biodegradable leather and plastic adhesive as described in claim 3, characterized in that, In step B1, the fatty alcohol glycidyl ether is lauryl glycidyl ether or glycidyl hexadecyl ether.

5. The anti-bulging biodegradable leather and plastic adhesive as described in claim 2, characterized in that, Step A1 also includes a metal catalyst, which is a tin-free system and is selected from one or more of bismuth neodecanoate, zinc laurate, calcium carboxylate, and magnesium carboxylate, with an amount of 0.005-0.08 wt% of the total monomer mass.

6. The anti-bulging biodegradable leather and plastic adhesive as described in claim 3, characterized in that, The polar modifier described in step B1 has a hydroxyl value of 120-350 mgKOH / g, a reaction temperature of 38-52℃, and a reaction time of 2.5-6h.

7. The anti-bulging biodegradable leather and plastic adhesive as described in claim 1, characterized in that, The cross-linked network formed after the adhesive is cured has an interfacial bonding strength of ≥12 MPa, a water vapor transmission rate of ≤280 g·m⁻²·day⁻¹, and a water absorption rate of ≤4.0wt%.

8. A method for preparing an anti-bulging biodegradable leather-plastic adhesive as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1) Cellulose pretreatment: Cellulose nanocrystals were prepared into an aqueous dispersion with a concentration of 2.0-3.0 wt% at 20-35℃ and dispersed at 250-350W for 12-20 min. Pre-coupling was performed with γ-aminopropyltriethoxysilane accounting for 30-50% of the total silane complex at pH 4.5-5.

5. Then, epoxy-terminated polyurethane emulsion was added and stirred for 25-40 min. S2) Addition of fluorine-free components: Add the fluorine-free polar modified epoxy compound dispersion dropwise over 10-20 min at a rate of 0.8-2.5 wt% of the main system, while stirring at 180-450 r / min for 12-25 min. S3) Mixing and homogenization: Add starch acetate and stir at 200-300 r / min for 8-15 min to mix evenly; S4) Crosslinking and curing: Heat to 60℃ and hold for 20 min, then heat to 70-80℃ and hold for 25-60 min. Add 0.1-0.5 wt% of curing catalyst to control the epoxy group to active hydrogen equivalent ratio to be 0.90-1.

10. S5) Post-treatment: Cool to 30-45℃, add the remaining silane compound after pre-hydrolyzing at pH 4.5-5.5 for 30-60 minutes, adjust the pH to 7.0-8.0, and perform degassing and maturation to obtain the finished product.

9. The preparation method of the anti-bulging biodegradable leather-plastic adhesive as described in claim 8, characterized in that, In step S4, the equivalent ratio of epoxy groups to active hydrogen is 0.90-1.00, the total holding time is 45-90 min, and the viscosity growth rate of the system is 150-250%.

10. The application of the anti-bulging biodegradable leather-plastic adhesive as described in any one of claims 1 to 7 in the bonding of leather and plastic.

Citation Information

Patent Citations

  • High-strength aqueous polyurethane adhesive

    CN102002337B

  • Environment-friendly adhesive for plywood and preparation method of adhesive

    CN105331328A

  • Water-based acrylic adhesive compositions

    CN112029448B

  • Preparation method of high-performance waterborne polyurethane adhesive for synthetic leather

    CN114574143A

  • Epoxy resin modified single-component moisture curing polyurethane adhesive and preparation method thereof

    CN115322725A